Ensuring Safety in Human-Robot Cooperation: Key Issues and Future Challenges - Sharkawy, Abdel-Nasser; Mahmoud, Khaled H.; Abdel-Jaber, Gamal T. (Peneliti Teknologi Teknik Indonesia, 2024)
Human-robot cooperation (HRC) is becoming increasingly essential in many different sectors such as industry, healthcare, agriculture, and education. This cooperation between robot and human has many advantages such as increasing and boosting productivity and efficiency, executing the task easily, effectively, and in a fast time, and minimizing the efforts and time. Therefore, ensuring safety issues during this cooperation are critical and must be considered to avoid or minimize any risk or danger whether for the robot, human, or environment. Risks may be such as accidents or system failures. In this paper, an overview of the safety issues of human-robot cooperation is discussed. The main key challenges in robotics safety are outlined and presented such as collision detection and avoidance, adapting to unpredictable human behaviors, and implementing effective risk mitigation strategies. The difference between industrial robots and cobots is illustrated. Their features and safety issues are also provided. The problem of collision detection or avoidance between the robot and environment is defined and discussed in detail. The result of this paper can be a guideline or framework to future researchers during the design and the development of their safety methods in human-robot cooperation tasks. In addition, it shapes future research directions in safety measures.